The paradox of community involvement: rebuilding Minamisanriku. Issue 6 (22nd June 2020) - Cheek, Wesley
Abstract : Purpose: The purpose of this paper is to identify the barriers to community participation in post-disaster reconstruction in Minamisanriku, Japan. Design/methodology/approach: This paper utilizes the extended case method. 31 in-depth, semi-structured interviews were conducted with local residents as well as 15 in-depth, semi-structured interviews with professionals working on reconstruction efforts. Multiple site visits were made to conduct participant observation and ethnographic research. The data from these interviews and fieldwork were triangulated with archival research. Findings: The results from this research show that at least six major barriers to community participation in post-disaster reconstruction were present in Minamisanriku. These barriers were: predetermined tsunami risk levels, a disaster reconstruction menu, existing patterns of government, construction of seawalls, an existing lack of participation and administrative mergers. These barriers were not a product of the disaster event itself, but rather of the pre-existing conditions in Minamisanriku, and Japan in general. Originality/value: This study pinpoints the actually existing barriers to the worldwide call for participatory measures and community involvement in post-disaster reconstruction.